Cana-de-açúcar: flutuação populacional de insetos-praga, fitopatometria e dinâmica temporal da ferrugem marrom sob diferentes adubações - Bonadiman, Paula Alberti (2021)
Sugarcane is one of the main Brazilian crops, present in small and large agricultural properties, with low and high technology. However, phytosanitary problems are a major concern to any degree, as in most of these problems, there is loss of product quality and / or reduced production. Thus, the objective of the work was to evaluate a population fluctuation of Saccharicoccus sacchari (Hemiptera: Pseudococcidae) and Mahanarva posticata (Hemiptera: Cercopidae), an infestation of complex the Diatraea saccharalis (Lepidoptera: Crambidaeaceae) and Colletotrichum falcatum (Glomerellales: Glomerellaceae) and record the occurrence of natural enemies, in two varieties of sugar cane, called regional “Palito” and commercial RB-867515, submitted to the presence and absence of chemical fertilization, during the caneplant cycle and first cane-soca. In addition, the objective was to develop and validate a standard area diagram with color photographs (SADcp) for brown rust, caused by the fungus Puccinia melanocephala (Uredinales: Puccinaceae) and a temporal dynamics of the disease. It was found that the variety RB-867515 had a higher incidence of S. sacchari, which was influenced by the average temperature and a greater number recorded in the months of May and April with a temperature of 23ºC. The cut of M. posticata occurred from April to August with an average of less than 7% and the infestation of the D. saccharalis/C. falcatum complex was 1% for both sugarcane cycles. The presence of the natural enemies Doru luteipes (Dermaptera: forficulidae), the mass of pupae of Cotesia flavipes (Hymenoptera: Braconidae), coccinellids (Coleoptera: Coccinellidae), chrysopids (Neuroptera: Chrysopidae) and entomopathogenic Aspergillus fungus were recorded. The diagram proposed in this study serves to assist in the visual estimate of the severity of brown rust on sugarcane leaves. As for the temporal dynamics, a brown rust occurred in the months taken, with greater severity in the colder seasons between May and August (20 to 22ºC). Brown rust was identified in the two varieties of sugarcane, but one RB867515 variety was less intense and chemical fertilization increased the disease severity in the Palito variety.